Structural and mechanical properties of nanocrystalline Zr co-sputtered a-C(:H) amorphous films - Escudeiro, A. (2014)
The aim of this study was to investigate the effect of Zr as alloying element to carbon films, particularly in respect to film structure and mechanical properties. The films were deposited by magnetron sputtering in reactive (Ar + CH4) and non-reactive (Ar) atmosphere with different Zr contents (from 0 to 14 at.%) in order to achieve a nanocomposite based films. With an increase of Zr content a broad peak was observed in X-ray diffraction spectra suggesting the presence of nanocrystalline (nc) ZrC phase for the coatings with Zr content higher than 4 at.%. The application of Scherrer formula yielded a grain sizes with a dimension of 1.0–2.2 nm. These results were supported by X-ray photoelectron spectroscopy showing typical charge transfer at Zr-C nanograins and carbon matrix interface. The nc-ZrC phase was also observed by transmission electron microscopy. The hardness of the coatings was approximately independent of Zr content. However, the Young modulus increased linearly. The residual stress of the coatings was strongly improved by the presence of nc-ZrC phase embedded in the a-C matrix. Finally, the incorporation of H into the matrix led to denser and harder films.